Preserving and promoting the cultural values of Vietnam’s traditional Ao Dai - Ngo Thi Viet Ha (Journal of State Management, 2024)
The traditional Ao Dai is deeply intertwined with the history and culture of Vietnam and has become one of the country's “cultural ambassadors.” The Oxford Dictionary has also included the Ao Dai as a distinctive product of Vietnam. The article summarizes the history and development of the dress through various periods, outlines the current state of efforts to preserve and promote its value in Vietnam, highlights the achievements, and identifies the challenges that need to be addressed. Based on this, the author proposes several solutions to enhance the effectiveness of preserving and promoting the value of this cultural heritage.